2019
DOI: 10.14221/ajte.2018v44n5.3
|View full text |Cite
|
Sign up to set email alerts
|

Halliday’s View of Child Language Learning: Has it been Misinterpreted?

Abstract: This paper gives a brief summary of Halliday's theory of how children learn to talk, illustrating the development of children's language from the microfunctions through the macrofunctions and into the metafunctions of adult language. The paper points to a possible source of the misinterpretation of Halliday's theory in the work of Frank Smith (1983), which appears to have "trickled down" into some of the textbooks written for pre-service teachers in Australia. Links are made to teachers' knowledge about langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Educators may consider how, through their own talk, they create particular contexts in which infants may or may not actively participate in making meaning from the picture book text. By listening carefully and mindfully to the verbal contributions of infants during shared reading, educators can gain valuable insights into how infants express their own funds of knowledge as they interpret the visual images they encounter (Halliday, 2004;Painter, 1984Painter, /2015Thwaite, 2019;Torr, 2015). Such insights can guide educators in planning further rich and engaging learning experiences, based on infants' own interests and background knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Educators may consider how, through their own talk, they create particular contexts in which infants may or may not actively participate in making meaning from the picture book text. By listening carefully and mindfully to the verbal contributions of infants during shared reading, educators can gain valuable insights into how infants express their own funds of knowledge as they interpret the visual images they encounter (Halliday, 2004;Painter, 1984Painter, /2015Thwaite, 2019;Torr, 2015). Such insights can guide educators in planning further rich and engaging learning experiences, based on infants' own interests and background knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…SFL theory has been widely used in educational research because it makes systematic connections between social and linguistic behaviour. SFL posits an underlying organising principle determining young children's transition from prelinguistic communication to adult-like words and structures, thus resolving an apparent discontinuity between adult talk and child talk (Halliday, 2004;Painter, 1984;Thwaite, 2019;Torr, 2015).…”
Section: A Language-based Theory Of Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…They further asserted that a wellconstructed test needs to sample tasks consistent with those in TLUS, or otherwise, its authenticity and construct validity might be questionable. On the other hand, as the results of the study indicated, TOEFL iBT speaking test fails to measure its applicants' skill in performing, at the very least, the heuristic function of language which is typically carried out through questioning (Thwaite, 2019). From Bachman and Palmer's perspective, negligence of applicants' questioning skill, in other words, would also point out traces of inconsistency between the test tasks and those in TLUS, threatening the authenticity, content validity, generalizability, construct validity, and, as a result, the usefulness of the tests.…”
Section: Concerns About Toefl Ibt Speaking Testmentioning
confidence: 92%
“…to demonstrate another language use that Halliday did not find in his study. This is understandable since Halliday based his theory on his observations of his son Nigel up to the age of 18 months only (Thwaite, 2019). This technique found in the Filipino boy appears to reflect the diversionary function of child language as posited by Canadian psycholinguist Frank Smith (Thwaite, 2019).…”
Section: Demonstration Of Models Of Child's Use Of Languagementioning
confidence: 96%